2018
DOI: 10.1038/s41434-018-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV-based lentivirus-mediated vasoactive intestinal peptide gene delivery protects against DIO animal model of Type 2 diabetes

Abstract: Type 2 diabetes mellitus (T2DM) is characterised by insulin resistance, glucose intolerance and beta cell loss leading to hyperglycemia. Vasoactive intestinal peptide (VIP) has been regarded as a novel therapeutic agent for the treatment of T2DM because of its insulinotropic and anti-inflammatory properties. Despite these beneficial properties, VIP is extremely sensitive to peptidases (DPP-4) requiring constant infusion or multiple injections to observe any therapeutic benefit. Thus, we constructed an HIV-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Antiapoptotic and insulinotropic functional properties of VIP have recently been demonstrated using a lentiviral vector (LentiVIP) in the animal model of T2DM. 38 To test these vectors in combination for STZ-induced diabetes, Len-tiINS and LentiVIP gene therapy vectors (LentiINSVIP) were delivered to diabetic Wistar rats to assess the efficacy of the combinatorial gene therapy approach in reducing blood glucose. Despite the significant reduction in non-fasting blood glucose of diabetic rats that received LentiVIP alone (compared to LentiLacZ-injected rats), concurrent administration of LentiINS and LentiVIP vectors were more effective than their individual injections (Figure 4A).…”
Section: Combinatorial Use Of Lentiins and Lentivip Vectors (Lentiinsvip) Was More Effective In Reducing Non-fasting Blood Glucose Than Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiapoptotic and insulinotropic functional properties of VIP have recently been demonstrated using a lentiviral vector (LentiVIP) in the animal model of T2DM. 38 To test these vectors in combination for STZ-induced diabetes, Len-tiINS and LentiVIP gene therapy vectors (LentiINSVIP) were delivered to diabetic Wistar rats to assess the efficacy of the combinatorial gene therapy approach in reducing blood glucose. Despite the significant reduction in non-fasting blood glucose of diabetic rats that received LentiVIP alone (compared to LentiLacZ-injected rats), concurrent administration of LentiINS and LentiVIP vectors were more effective than their individual injections (Figure 4A).…”
Section: Combinatorial Use Of Lentiins and Lentivip Vectors (Lentiinsvip) Was More Effective In Reducing Non-fasting Blood Glucose Than Tmentioning
confidence: 99%
“…[31][32][33][34] Currently, lentiviral vector-mediated therapeutic gene delivery is already underway for the treatments of both T1DM 35,36 and T2DM. 37,38 Recent studies concerning liver-directed gene therapy revealed that basal insulin requirements for T1DM could be met using lentivirus-mediated furin-cleavable insulin gene delivery to hepatocytes. 39,40 This approach was aimed at obviating the need for longacting insulin analogs in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 is the most extensively characterized human lentivirus used as the backbone for lentiviral-vectored gene therapies. 119,120 Compared to retroviral vectors, lentiviral vectors have superior properties, such as the ability to transduce diving and nondividing cells, high infection efficiency, and low probability of insertional mutagenesis. 121 Contrary to AAV (weakly immunogenic) and Ad-vectored (highly immunogenic) therapies, lentiviral vectors are fairly nonimmunogenic and provide long-term gene expression due to permanent integration into the host genome.…”
Section: Lentivirus Structure and Vector Designmentioning
confidence: 99%
“…Expression of a mutant glucokinase (mGCK), which is an enzyme critical for glucose metabolism, by injection (SC) of adenovirus-based vector resulted in steady decrease in blood glucose over a long period (12-70 days) without inducing hypoglycaemia [66]. Expression of vasoactive intestinal peptide (VIP) by injection (IP) of HIV-based lentiviral vector encoding VIP improved insulin sensitivity, glucose tolerance, and reduced serum triglyceride/cholesterol levels [67]. ANGPTL8 gene delivery by ultrasound-targeted microbubble destruction promoted b-cells proliferation, expanded the b-cell mass, improved glucose tolerance, and increased the fasting blood insulin level in a diabetic rat model [68].…”
Section: Gene Therapy With Other Novel Targetsmentioning
confidence: 99%